Representações sociais de discentes de enfermagem sobre ser enfermeiro - Aneilde Maria Ribeiro de Brito (2008)
The purpose of this study was to analyze the structures about being anurse of nursing students social representations of five private SuperiorEducation Institutions of Belo Horizonte created in the period between2003 and 2004. It was adopted as a theoric methodological referential the Social Representation Theories proposed by Moscovici and by the Theory of the Central Nucleus elaborated by Jean-Claude Abric, in the Social Psychology perspective. Data were obtained by the use of twoquestionnaires. The first wanted to know the socio-demographic profile ofthese students, while the second, based on the free evocation technique,wanted to learn the social representation due to the induction term being a nurse. 430 students constituted the sample, distributed between the 1st and 6th periods of the nursing courses of the mentioned institutions, what consisted of 45,6% of the total population. The profile description of these students were analyzed by simple attendance, and the structures obtained by free evocations were processed by the software Ensemble de Programmes Permettant des Evocations (EVOC) and analyzed by the four house board technique created by Pierre Vergès. There was a major of young, female, single, and coming from public schools students. Aconsiderable number of these students practice some kind of remunerated activity and almost half of the ones who worked, were working in the nursing area. The building of the structures starting from the students evocations leads us to possible central nucleus toward the elements caring and responsibility which were found strongly connected by elements that translate affectionate values and attitudes, as for theintegrality of the rendered assistance, anchored in the historical, culturaland formatives contingencies of the studied individuals. Besides that, theevocations management, professionalism, work, realization, attentionand respect, were found, providing them a peripheral role. In face of theseimage verify that the students perceptions related to being a nurse hasbeen modified through time, even though it has been done slowly andgradually. Through this perspective its necessary to review concepts,update values and make choices to a critical-reflective professionalsformation, socially committed with group and individual works in the healtharea.